IMPROVED ROAD PERFORMANCE THROUGH THE IMPLEMENTATION OF ROUTINE ROAD MAINTENANCE MANAGEMENT SYSTEM - Triyono, AR. Hanung; Hermani , Wahyuningsih Tri; Amrulloh, Nanang Syarifuddin; Setyawan, Ary (Journal of Applied Engineering Science, 2024)
Road infrastructure development is carried out to be able to serve the flow of goods and passengers smoothly, safely, and comfortably. Infrastructure maintenance is needed to keep roads always in good condition. The road infrastructure consumes a significant amount of budget, both for road maintenance and improvement. The Central Java Provincial Government, through the Public Works Service for Highways and Civil Works, has a prioritization sequence to maintain road conditions to facilitate smooth, safe, and comfortable traffic. Continuous and sustainable maintenance of constructed roads is necessary to ensure their stability. Therefore, a large budget is required to carry out this maintenance. In 2023, the budget requirement for routine road maintenance amounted to IDR 441.246.000.000,00. However, the actual budget realization for 2023 was only IDR 125.686.108.000,00, fulfilling just 28,48% of the calculation model using from using analysis for Planning, Programming, and Budgeting (P/KRMS analysis) application. Analysis results indicate that the budget realization for routine road maintenance in 2023 did not meet the requirement to maintain a stable road surface, as evidenced by a 1,61% decrease in road surface condition from 2022. The Central Java Provincial Public Works Service for Highways and Civil Works faces this challenge by maximizing the involvement of the Community Group for Highways Development (Mas BIMA) in expediting the handling process.
Keywords: routine, maintenance, road, budget, sustainable